The Thermal Stability of Intermetallic Compounds in an As‐Cast SX Co‐Base Superalloy1. Issue 6 (17th July 2014) - Lopez‐Galilea, Inmaculada; Zenk, Christopher; Neumeier, Steffen; Huth, Stephan; Theisen, Werner; Göken, Mathias
<x xml:space="preserve">Abstract</x> The nature and stability of intermetallic phases in a multi‐component γ/γ′ Co‐base superalloy is investigated. At least three kinds of unwanted intermetallic phases form due to the segregation of Al, Ta, Ti, Si, and Hf during casting in the interdendritic areas in addition to γ and γ′. One of the intermetallic phases that shows a blocky shape, contains high content of Ta, Hf, and Ti and has been identified as a topologically close‐packed Laves phase. A B2 phase appears as relatively big pools and in some cases contains needle‐shaped precipitates with high content of Al and Ti. The thermal stability of these intermetallic phases is studied in this work under defined heat treatments. The needle‐shaped precipitates already dissolve at 1000 °C, whereas the B2 phase is dissolved only at higher temperatures of 1200 °C. Small amounts of Laves phases remained stable during aging at 1200 °C for 25 h. The prediction of phases as well as their stability is also checked by the CALPHAD method. The TCNi5 database, containing the description of Co3(Al, W), predicts the presence of the observed intermetallic phases; however, the predicted main transformation temperatures for these phases differ from the experimentally obtained values.